Salivary cotinine concentration and carbon monoxide levels in young adults smoking midwakh in comparison with cigarette smokers. Issue 2 (9th July 2018) - Shaikh, Rizwana Burhanuddin; Sreedharan, Jayadevan; Al Sharbatti, Shatha; Muttappallymyalil, Jayakumary; Lee, Lily; Weitzman, Michael
Abstract : Objectives: To estimate and compare the salivary cotinine levels using a semiquantitative method, called NicAlert, between three groups: non-smokers, daily smokers of cigarettes and daily smokers of midwakh, and to compare the carbon monoxide (CO) levels among these groups. Materials and methods: A total of 159 adult male volunteers aged 20 and above were included, with 54 current cigarette smokers, 52 current midwakh smokers and 53 non-smokers. Estimate of breath carbon monoxide and salivary cotinine were collected, as well as sociodemographic characteristics and details of smoking habits and second-hand smoke exposure among participants. Institutional review board approval was obtained and data were analysed using SPSS V.21 with the Kruskal-Wallis test used to obtain differences in the distribution. Results: There was no significant difference in the median breath CO and salivary cotinine levels between cigarette and midwakh smokers. Levels of breath CO were significantly higher in cigarette and midwakh smokers as compared with non-smokers (19.5, 17.5 and 6.0, respectively, p<0.05); the same relationship was observed for cotinine levels among cigarette and midwakh smokers as compared with non-smokers (4.0, 3.0 and 0.0, respectively, p≤0.05). Additionally, the values of both salivary cotinine and breath CO increased with the frequency of tobacco use. Conclusion: These are the first data that we are aware of that demonstrate that in terms of at least two key biomarkers of tobacco use, there are comparable levels of exposure between cigarettes and midwakh users, demonstrating a need for intensified attention to the use of midwakh.